2015
DOI: 10.2139/ssrn.2698317
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Firm Size on Earnings Management: A Study of Textile Sector of Pakistan

Abstract: The study was conducted to evaluate the impact of firm size on earnings management for the textile sector of Pakistan. For this purpose annual ten years data was obtained from 2004 to 2013 for fifty selected firms from the textile sector of Pakistan. Natural logarithm of total assets was used as the proxy of firm size. On the other hand earning management was the dependent variable of this study. Earnings management was measured through discretionary accruals by using modified Jones model. Descriptive statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
38
0
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 26 publications
10
38
0
12
Order By: Relevance
“…The results of the study support agency theory which states that the larger the company, the greater information asymmetry and agency conflict faced by the company. The results of this study are in line with the research of Barton and Simko (2002) and Ali et al (2015). Their study found a positive relationship between company size and earnings management, the larger the company, the more likely management to do earnings management because large companies are under big pressure to fulfill the expectations of financial analysts.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results of the study support agency theory which states that the larger the company, the greater information asymmetry and agency conflict faced by the company. The results of this study are in line with the research of Barton and Simko (2002) and Ali et al (2015). Their study found a positive relationship between company size and earnings management, the larger the company, the more likely management to do earnings management because large companies are under big pressure to fulfill the expectations of financial analysts.…”
Section: Discussionsupporting
confidence: 89%
“…Political costs occur high due to the profitability of the company that can attract the attention of the media and consumers. Barton and Simko (2002) and Ali et al (2015) have used agency theory to explain the relationship between firm size and earnings management. Barton and Simko (2002), Ali et al (2015), and Turegun (2016) found a positive relationship between company size and earnings management large companies tend to do earnings management because large companies are under great pressure to fulfill the expectations of financial analysts.…”
Section: Introductionmentioning
confidence: 99%
“…Source: Authors' computation, 2018. this study. It corroborated previous conclusions in the literature, notably the study of Ali et al [33]. They found an inverse association between leverage (LEV) and earnings persistence and share price (SP) of listed manufacturing firms in Nigeria.…”
Section: Tobin's Q and Earnings Persistencesupporting
confidence: 91%
“…This findings supports many of the existing literature like (Ajit, Malik, & Verma, 2013); (Roy, 2016). On the other hand, results advocated a momentous negative association between firm size and earnings management which is fairly in line with the current literature like (Ali, Noor, Khurshid, & Mahmood, 2015). The study moreover found the optimistic relation between firm's age and earnings management.…”
Section: Resultssupporting
confidence: 91%
“…In this position, one dominant issue that remain on the front burner is how to build up and maintained investors' confidence in the domestic economy through transparent financial reporting (Fodio, Ibikunle, & Oba, 2013). Study on earnings management is one such instrument which will enable the regulatory bodies in the country to ensure that reported accounting figures are representative 8 of true and fair picture of financial affairs of firm in particular and economy in general (Roy & Debnath, 2015a). The practice of earnings management within the firm may leave challenge before the investors (Ajay & Madhumathi, 2015).…”
Section: Introductionmentioning
confidence: 99%